The crisis crunch - investigating the effect of social media on ingroup favouritism of prosocial behaviour in a crisis and the possible mediating role of empathy and self-esteem - Tan, Boon Wee (Nanyang Technological University, 2021)
The rise of social media use has gradually changed what is perceived as a social norm, influencing the behaviour of individuals. Consequently, multiple research have found that social media use have both positive and negative influence, affecting an individuals’ decision in prosocial behaviour. The present study examined the relationship between social media use and prosocial behaviour in a crisis and investigated the relationship between social media use and ingroup favouritism in prosocial behaviour in a crisis as well. Additionally, empathy and self-esteem were examined as mediators of this relationships. Results indicated that social media use do not have a significant relationship with prosocial behaviour. There was no significant relationship between social media use and ingroup favouritism as well. Noteworthily, results found that empathy would mediate the relationship between social media use and prosocial behaviour; social media use results in greater empathy which in turns results in greater prosocial behaviour. However, empathy would not mediate the relationship between social media use and ingroup favouritism. Self-esteem was found not to mediate any relationship and was not affected by social media use. These findings highlight the importance of empathy in encouraging prosocial behaviour through social media use.